2015
DOI: 10.5897/ijmms2014.1101
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the pattern of antibiotics use in pediatrics ward of Dessie Referral Hospital, North East Ethiopia

Abstract: The main purpose is to assess the prescribing practice of antibiotic in pediatrics ward of DRH, North East Ethiopia. Methods: A hospital-based retrospective cross sectional study was used to assess patient cards for the past 1 year (June 2012-May 2013). Results: About 98 % of pediatrics was prescribed with at least one antibiotic. The most common diagnoses were severe pneumonia (19.6%) and Acute Gastroenteritis (AGE) with some dehydration (10.3%). The most commonly prescribed single antibiotics was crystalline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
(14 reference statements)
2
11
0
Order By: Relevance
“…A similar picture was found in Ethiopia [14] and Nigeria. [15] Possible explanations include drug availability, the presence of nonspecific infections, such as upper respiratory tract infections, empirical treatment, and prophylactic use.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…A similar picture was found in Ethiopia [14] and Nigeria. [15] Possible explanations include drug availability, the presence of nonspecific infections, such as upper respiratory tract infections, empirical treatment, and prophylactic use.…”
Section: Discussionsupporting
confidence: 69%
“…[13,23] The reasons for parenteral use included the clinical condition of the patient, the need for rapid action, the belief that injectable antibiotics are more potent, and the availability of injectable antibiotics. [14,16,23,24] Children <5 years old received antibiotics more often than older children, possibly owing to more severe clinical conditions in younger patients. [25] In addition, regardless of laboratory confirmation, clinical conditions played an important role in the use of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies in Ethiopia and Tanzania showed that pneumonia was implicated as the most common reason for hospitalisation. [16][17][18][19] This implies that pneumonia is a major cause of morbidity and hospitalisation among children in these African countries.…”
Section: Discussionmentioning
confidence: 99%
“…Referral Hospital showed that 76% of antibiotics were given through parenteral route with practice of parenteral to oral shift during discharge 23 (7.9%) of cases [26]. Retrospective assessment conducted in Mekelle general hospital showed that the percentage of encounters with antibiotic injections at inpatient departments 172 (95.2%) out of 181 sampled antibiotic prescribed were parenteral formulations [27].…”
Section: Strength and Weakness Of The Studymentioning
confidence: 99%
“…• The data was collected using a structured self-administered pre-tested questionnaire • Adequate sample size was applied according to single population proportion formula • Data collators were trained health professional • Data quality is controlled throughout the study Referral Hospital showed that 76% of antibiotics were given through parenteral route with practice of parenteral to oral shift during discharge 23 (7.9%) of cases [26]. Retrospective assessment conducted in Mekelle general hospital showed that the percentage of encounters with antibiotic injections at inpatient departments 172 (95.2%) out of 181 sampled antibiotic prescribed were parenteral formulations [27].…”
Section: Strength and Weakness Of The Studymentioning
confidence: 99%